Ретроспективний аналіз ефективності лікування мікроаденом гіпофіза у жінок, що не народжували, з урахуванням фракціонування пролактину й корекцією недостатності лютеїнової фази - Трушкевич, О.О. (Таврический медико-биологический вестник, 2012)
Для решения поставленной цели проведено комплексное обследование 40 нерожавших женщин, в возрасте 18-26 лет с диагностированными у них пролактиномами гипофиза. 20-ти пациенткам первой группы проводилось лечение по общепринятой методике - терапия агонистами дофамина (Достинекс) до нормализации уровня пролактина в сыворотке крови и исчезновения клинической симптоматики гиперпролактинемии, и 20-ти – по разработанной нами методике - до нормализации уровня “lіttle”- фракции пролактина с последующей коррекцией недостаточности лютеиновой фазы. Предложенная методика лечения микроаденом гипофиза длительной терапией (18-36 месяцев)
микродозами Достинекса (0.125 мг ) под контролем “lіttle”- фракции пролактина позволяет получить значительный клинический эффект в 40 % случаев, что проявляется уменьшением размеров микроаденомы вплоть до полного исчезновения данного образования у 4-х пациенток. For the decision of the put purpose a complex inspection is conducted 40 unparous women, in age 18-26 years with diagnosed for them prolactinomas of hypophysis. Treatment of the first group was conducted patients (n=20) on the generally accepted method is therapy by the agonists of dofamine (Dostineks) to normalization of level of prolactin in the whey of blood and disappearance of clinical symptoms of hyperprolactinemia, and 20 patients treated by the innovation method, which lead to normalization of level of “lіttle”- fraction of prolactin with the subsequent correction of insufficiency lutein faze.Offered method of treatment of microprolactinomas of hypophysis by the protracted therapy (18-36 months) microdosis of Dostineks (0.125 mg ) under control allows “lіttle”- fraction of prolactin to get a considerable clinical effect in 40 % cases, that shows up diminishing of sizes of microprolactinomas up to complete disappearance of this tumor in 4th patients.